Effects of eight weeks of aerobic exercise and taking caraway supplement on C-reactive protein and sleep quality in obese women - Mohammadkhani, Parisa Ghiasvand; Irandoust, Khadijeh; Taheri, Morteza; Mirmoezzi, Masoud; Baić, Mario (Biological rhythm research, 2021)
Using sport exercise with herbal supplements is one of the recommended methods for controlling obesity and its complications. The purpose of this study was to investigate the effects of eight weeks of aerobic exercise and consuming caraway on C-reactive protein (CRP) and sleep quality in obese women. In aquasi-experimental study, 30 obese women were selected by convenience sampling. Then, they were randomly divided into 4 groups: supplement-exercise (SE); placebo-exercise (PE); exercise (E), and control. The supplement group consumed 50mg of caraway per kilogram of body weight daily, and the placebo-exercise group consumed the same amount of starch powder. Aerobic exercises were performed for 8 weeks, three sessions aweek with an intensity of 65-75% of maximum heart rate. The level of CRP was measured by special laboratory kits. Sleep quality was evaluated by using the Pittsburgh Sleep Quality Index (PSQI) before and after the intervention. It was indicated that waist to hip ratio (WHR) of the SE group was significantly different with all the groups (p < 0.05). Body fat percent (BFP) of the SE group was also significantly different with control group (p = 0.042). WHR in SE group was significantly different with control (p = 0.006) and exercise group (p = 0.021). The CRP of the SE group was significantly different from that of the control group (p = 0.000), and the sleep quality of the SE group was significantly different only the control group (p = 0.001). Consuming caraway with aerobic exercise has positive effects on the level of C-reactive protein and sleep quality.